Gastroduodenal myoepithelial hamartoma - Puig, Roberto; Reissenweber, Nelson; Sarroca, Carlos; Gary, Ruben (Cirugía del Uruguay, 1975)
A brief selection of bibliographical material was made on the subject of gastroduodenal mioepithelial hamartomas, bearing in mind Prof. Juan Francisco Cassinelli's teaching which associates heterotopic pancreas. Brunnerian adenomas and their intermediate forms. Three cases are described: two localized submucous gastric lesions and one double gastric and duodenal lesion. -The fundamental lesion is a small tumorlike nodule composed of ectopic focus of glandular and ductal tissue in a smooth muscle stroma, resulting from an undetermined development anomaly. Many cases are asymptomatic and the clinical symptoms are variable. X-Rays usually show a small ovoidal lacunar appearance, often with central umbilication. The treatment recommended is local removal, under histopathological peroperative control.